IDENTIFIKASI SPESIES LALAT BUAH (Diptera: Tephritidae) PADA BUAH YANG DI PERDAGANGKAN DI PASAR MODERNPASIR PENGARAIAN KECAMATAN RAMBAHKABUPATEN ROKAN HULU - Utama, Rizki Putra; Yolanda, Rofiza; Lubis, Riki Riharji (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aims of study was to identify the fruit flies (Diptera: Tephritidae) species on fruit that traded in Pasir Pengaraian Modern Market Rambah District Rokan Hulu Regency. Study was conducted in October to December 2014, using survey method by way of fruitfly eggs spawned in several pieces that chilies red, mango, papaya, bananas and tomatoes. Results obtained three species of fruitfly Bactrocera carambolae, B. dorsalis and B. umbrosa. B. carambolae found in mangoas muchas 7 individual, B. dorsalis found in mangoas much as 3 individual and B. umbrosa found inred chiliesas much as10 individuals.